KESADARAN HUKUM MASYARAKAT DALAM PENDAFTARAN TANAH DI KECAMATAN ATAMBUA SELATAN KABUPATEN BELU - Hittu, Olga Sarlien; Asnawi, Norani; Dai, Hermanwati A Y (Petitum Law Journal, 2025)
This study examines the legal understanding of residents of South Atambua District, Belu Regency (NTT), regarding land registration using empirical legal methods. Through indicators of knowledge, understanding, attitude, and legal behavior, it was revealed that most respondents (62 heads of families in the sample) have basic knowledge about the importance of land certificates and the PTSL program, but their understanding of technical procedures, requirements, and costs is still very limited, especially among residents with low education (39% high school education, 31% junior high school education) and low income (average IDR 2.1 million per month). Although there is a positive attitude towards the obligation to certify (60 respondents agree), this is hampered by the view of complicated bureaucracy, high costs, and dependence on government programs. Behavioral patterns show that people comply with official procedures, but independent initiatives are still very few due to external factors (land disputes, economic factors) and also internal factors (limited human resources, slow bureaucracy). Structural challenges such as low legal literacy, a non-digital administrative system, and lack of socialization further exacerbate the lack of public knowledge.